Perbandingan Metode KNN, Naive Bayes, dan Regresi Logistik Binomial dalam Pengklasifikasian Status Ekonomi Negara - N. K. Kutha Ardana; Ruhiyat Ruhiyat; Nurfatimah Amany; Teofilus Kevin Irawan; Raymond Raymond; Rizalius Karunia; Syifa Fauzia (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
The classification of a country's economic status as developed or developing often involves factors such as life expectancy and its underlying variables. This research aims to compare the performance of three machine learning algorithms, namely KNN (K-Nearest Neighbors), naive Bayes, and binomial logistic regression, in classifying the economic status of countries as developed or developing. The data used in this study is